2013
DOI: 10.5604/17322693.1085135
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and local mechanisms leading to cachexia in cancer

Abstract: Cachexia is a multifactorial syndrome of atrophy of skeletal muscle and adipose tissue, resulting in progressive loss of body weight associated with low quality of life and poor prognosis in cancer. Studies on experimental animal models and observations on patients have shown that the soluble factors secreted by tumor cells and tissues of the patient can participate in regulation of the wasting process. Cachexia is often accompanied by anorexia, which is caused by predominance of signals inhibiting appetite in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Gluconeogenesis is promoted by the high level of lactate derived from tumour glycolysis and is insensitive to physiological inhibitor stimuli such as the administration of glucose itself. Gluconeogenesis is an extremely energy-demanding process [ 45 ] and may be considered an important mechanism of the increased energy consumption in cancer patients. Gluconeogenesis also influences the protein metabolism, recruiting and therefore reducing amino acid levels.…”
Section: Physical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gluconeogenesis is promoted by the high level of lactate derived from tumour glycolysis and is insensitive to physiological inhibitor stimuli such as the administration of glucose itself. Gluconeogenesis is an extremely energy-demanding process [ 45 ] and may be considered an important mechanism of the increased energy consumption in cancer patients. Gluconeogenesis also influences the protein metabolism, recruiting and therefore reducing amino acid levels.…”
Section: Physical Aspectsmentioning
confidence: 99%
“…A central alteration of the protein metabolism in cancer cachexia is the reduction of lean body mass. The depletion of lean mass is caused by an increase of muscular protein degradation without a correspondent increase of protein synthesis, which remains normal or is even slightly reduced [ 46 ]. There are three main mechanisms of muscle proteolysis: the lysosomal (cathepsin) proteolytic pathway, the calcium-activated system and the ubiquitin-proteasoma proteolytic pathway, which is the most important mechanism of protein degradation in cachexia [ 47 ].…”
Section: Physical Aspectsmentioning
confidence: 99%
“…Saikosaponins are isolated as active ingredients of Radix Bupleuri, showed potent anti-inflammatory activities [ 47 ], anti-ulcerative [ 48 ], platelet activation inhibitory [ 49 ], corticosterone secretory [ 50 ], hepatoprotective [ 51 ], and nephroprotective [ 52 ] activities through their potent free radical scavenger effects, the antioxidant effects. Dehydroglyasperin D (DGD) is isolated from Glycyrrhizae also possessed the most potent antioxidant activity [ 53 ]. The present results suggested that BZYQ might effectively inhibited lipid peroxidation in muscle tissues, and acted directly or interacted with endogenous antioxidants for synergistic effects to defend against fatigue caused by PTX treated.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Alterations in protein metabolism determine the increase in serum levels of protein-inducing factors and increased protein degradation in muscle tissue with loss of lean mass that is already evident at the early stages of the disease. 7 In addition, the production of lipid-metabolising factor induces consequent lipolysis that results in patients’ progressive weight loss. 8 Pro-inflammatory cytokines contribute to the pathophysiology of neoplastic cachexia, such as interleukins 1 and 6, tumor necrosis factor alpha, and interferon gamma, which in turn results in an increase in C-reactive protein (CRP), haptoglobin and ceruloplasmin that are responsible for increased fatty acid turnover and muscle proteolysis.…”
Section: Introductionmentioning
confidence: 99%